Urachal Carcinoma with Peritoneal Dissemination Treated with Chemotherapy and Surgical Resection Leading to Prolonged Survival with No Recurrence. (13th June 2018) - Yasui, Masato; Jikuya, Ryosuke; Tatenuma, Tomoyuki; Muraoka, Kentaro; Umemoto, Susumu; Kawai, Masaki; Kouno, Tsutomu; Kishida, Takeshi
Abstract : A 56-year-old man was admitted to our hospital for urachal carcinoma with peritoneal dissemination. He received first-line chemotherapy with gemcitabine and cisplatin. After the fifth cycle, a computed tomography (CT) scan revealed abdominal fluid, and his serum tumor marker levels were increased. The patient was started on second-line therapy with FOLFIRI. After 11 cycles, his tumor decreased in size and no new metastatic lesions were detected. The patient underwent complete tumor resection with partial cystectomy and pelvic lymph node dissection. The tumor was removed, along with adhering surrounding organs, including the omentum, peritoneum, abdominal rectus muscle, and vermiform appendix. Although pathological examination confirmed peritoneal dissemination, his tumor markers normalized soon after surgery. The patient has survived 62 months after surgery without any adjuvant therapy and with no evidence of recurrence. To our knowledge, this is the longest duration of survival without recurrence of a patient with urachal carcinoma with peritoneal dissemination who received multimodal therapy.